2020
DOI: 10.1002/sim.8537
|View full text |Cite
|
Sign up to set email alerts
|

Improving coverage probabilities for parametric tolerance intervals via bootstrap calibration

Abstract: Statistical tolerance intervals are commonly employed in biomedical and pharmaceutical research, such as in lifetime analysis, the assessment of biosimilarity of branded and generic versions of biopharmaceutical drugs, and in quality control of drug products to ensure that a specified proportion of the products are covered within established acceptance limits. Exact two-sided parametric tolerance intervals are only available for the normal distribution, while exact one-sided parametric tolerance limits are ava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…To assess the inter-rater agreement of the histological scorings, we used one-way intraclass correlation (ICC) coefficient by means of R package irr (http://cran.r-project.org/package=irr). In order to test the hypothesis of the ICC being >0.5 against the alternative, we needed a minimum of 40 histology images to reach the power of 0.8 with a type I error of 0.05 36. According to Landis and Koch benchmarks,37 ICC of <0.2, 0.2 to 0.4, >0.4 to ≤0.6, >0.6 to 0.8 and >0.8 was considered ‘poor’, ‘fair’, ‘moderate’, ‘good’, ‘substantial’ and ‘almost perfect’, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To assess the inter-rater agreement of the histological scorings, we used one-way intraclass correlation (ICC) coefficient by means of R package irr (http://cran.r-project.org/package=irr). In order to test the hypothesis of the ICC being >0.5 against the alternative, we needed a minimum of 40 histology images to reach the power of 0.8 with a type I error of 0.05 36. According to Landis and Koch benchmarks,37 ICC of <0.2, 0.2 to 0.4, >0.4 to ≤0.6, >0.6 to 0.8 and >0.8 was considered ‘poor’, ‘fair’, ‘moderate’, ‘good’, ‘substantial’ and ‘almost perfect’, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…In order to test the hypothesis of the ICC being >0.5 against the alternative, we needed a minimum of 40 histology images to reach the power of 0.8 with a type I error of 0.05. 36 According to Landis and Koch benchmarks, 37 ICC of <0.2, 0.2 to 0.4, >0.4 to ≤0.6, >0.6 to 0.8 and >0.8 was considered ‘poor’, ‘fair’, ‘moderate’, ‘good’, ‘substantial’ and ‘almost perfect’, respectively. Results of all statistical tests were considered significant at p<0.05.…”
Section: Methodsmentioning
confidence: 99%
“…This yields a reference sample of size n = 5255. The UACR data were analyzed in Zou and Young (2020), where the authors had established a one-sided upper tolerance limit of 0.7358 mg/g and suggested to classify adolescents with UACR values falling below it as "strictly normal." Interested readers may refer to the paper, and more background information is omitted here.…”
Section: Illustration I: Using Uacr Datamentioning
confidence: 99%
“…For illustrative purposes, we also treated the UACR data of size n = 5255 as our population, to which the exponential distribution gave a good fit (Zou and Young, 2020); that is, the shape parameter α = 1, but the rate parameter β was assumed unknown. We set c = 0.7358 and proceeded to estimate p = P β (X > c), which can be interpreted as the proportion of healthy adolescents with mildly increased UACR.…”
Section: Illustration I: Using Uacr Datamentioning
confidence: 99%
“…According to the review of the literature above, it can be found that the emphasis of Bootstrap methods has always been on calibrating CIs, prediction intervals, or some nonstandard TI procedures, with scant attention given to the calibration of TIs for non‐normal distributions (see, e.g., Fernholz & Gillespie, 2001; Zou & Young, 2020).…”
Section: Introductionmentioning
confidence: 99%